Application scenarios for a mobile hearing aid demonstrator with headphone form factor. - Denk, Florian; Simon, Lisa-Marie; Trautmann, Yara; Goicke, Stefanie; Albrecht, Jennifer; Andersen, Pernilla Kjær; Jürgensen, Lukas; Schönweiler, Rainer; Jürgens, Tim; Neher, Tobias; Husstedt, Hendrik (International Journal of Audiology, 2026)
Objective: To describe application scenarios of a mobile device that provides a practical means for showcasing potential hearing aid benefits. Design: A prototype of a hearing aid demonstrator based on circumaural headphones and a mobile signal processing platform was developed, providing core functions of a hearing aid, including several gain presets, in a hygienic, robust, and easy-to-use form factor. Speech intelligibility outcomes with the demonstrator and broadband level adaptations as potential fitting references were compared to outcomes with the own hearing aids of hearing-impaired participants. Furthermore, subjective assessments of the effect of the demonstrator were obtained at a public outreach event. Study sample: 20 experienced hearing aid users participated in the speech intelligibility outcome measurements. 54 citizens participated in the public outreach event. Results: Speech intelligibility measurements made with the demonstrator constituted a better predictor for typically achieved aided speech intelligibility outcomes than broadband level adaptations. Participants at the public outreach event reported that trying out the demonstrator changed their expectations of hearing aid benefits and improved their understanding of how hearing aids work. Conclusion: The developed demonstrator promises to be a useful tool for showcasing and probing benefits of hearing aids in clinical, public, and educational settings.